2019
DOI: 10.1016/j.ijcha.2019.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the clinical frailty scale on mid-term mortality in patients with ST-elevated myocardial infarction

Abstract: Background “Frailty” is associated with poor prognosis in ST-elevated myocardial infarction (STEMI). However, there is little data regarding the impact of the Canadian Study of Health and Aging Clinical Frailty Scale (CFS), a simple and semiquantitative tool for assessing frailty, on mid-term mortality in STEMI patients. Methods A total of 354 consecutive STEMI patients (mean age 69.8 ± 12.4 years; male 76.6%) who underwent percutaneous intervention between July 2014 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 27 publications
(29 reference statements)
1
11
0
1
Order By: Relevance
“…As expected, in our sample of older adults with pre-existing CHD our findings showed increased mortality as the rates and risk of frailty increase. These results are similar to those in CVD [12,16,25], acute coronary syndrome [31][32][33], and myocardial infarction [34], as well as after CVD interventions [35][36][37]. This lends credence to using the HFRS for observational research, or for applications with electronic medical records (EMR) to identify frailty using ICD-10-CM codes to determine who may be at greater risk for readmission or death.…”
Section: Resultssupporting
confidence: 60%
“…As expected, in our sample of older adults with pre-existing CHD our findings showed increased mortality as the rates and risk of frailty increase. These results are similar to those in CVD [12,16,25], acute coronary syndrome [31][32][33], and myocardial infarction [34], as well as after CVD interventions [35][36][37]. This lends credence to using the HFRS for observational research, or for applications with electronic medical records (EMR) to identify frailty using ICD-10-CM codes to determine who may be at greater risk for readmission or death.…”
Section: Resultssupporting
confidence: 60%
“…Studies have shown that frailty is an independent risk factor for the accelerated development of agerelated diseases in patients with CHD (5). Yoshioka et al (6) have found that intermediate mortality in patients with ST-segment myocardial infarction is associated with frailty. Frailty can be reversed with intervention, especially in the early stages (7).…”
Section: Introductionmentioning
confidence: 99%
“…An association between severe frailty and mid-term mortality was also observed in STEMI patients undergoing PCI. [ 57 ] In that study, 3.1% of the 354 patients were frail according to the CFS (≥6), and this was identified as an independent predictor of mid-term all-cause mortality (adjusted HR 2.46; 95% CI [1.52–3.98]), together with higher Killip score (adjusted HR 3.10; 95% CI [1.50–6.39]) and lower serum albumin concentrations (adjusted HR 4.29; 95% CI [2.16–8.51]).…”
Section: Frailty and Acute Coronary Syndromementioning
confidence: 99%